2011
DOI: 10.1111/j.1551-2916.2011.04849.x
|View full text |Cite
|
Sign up to set email alerts
|

Local Structure of Amorphous EuO–TiO2 Thin Films Probed by X‐Ray Absorption Fine Structure

Abstract: We have investigated the local structure of amorphous oxides in EuO–TiO2 system to understand the mechanism that gives rise to curious ferromagnetic properties recently observed in the system. X‐ray absorption spectroscopy has been performed on amorphous EuTiO3 and Eu2TiO4 thin films prepared by the pulsed‐laser‐deposition method. The Ti K‐edge X‐ray absorption near‐edge structure (XANES) and extended X‐ray absorption fine structure (EXAFS) data analyses reveal that the coordination number of Ti4+ in the amorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…5(a) and 5(c)] is characterized by an intense peak and a satellite structure, with an energy separation of ∼10 eV; for example, the major peak and satellite for the Eu L 3 edge are observed at 6972 and 6981 eV, respectively, as indicated by the vertical dashed lines. According to our previous Eu L 3 edge XAS study, 16 the major peak and satellite are attributable to the contributions from Eu 2+ and Eu 3+ ions, respectively. To estimate the relative contributions of Eu 2+ and Eu 3+ , the XAS for Eu L 3 edge was deconvoluted by the superposition of two Lorentzians and two arctangent functions, according to the procedure used by Godart et al 43 for the analysis of mixed valence in rare-earth intermediate compounds.…”
Section: Experimental Details and Sample Characteristicsmentioning
confidence: 65%
See 2 more Smart Citations
“…5(a) and 5(c)] is characterized by an intense peak and a satellite structure, with an energy separation of ∼10 eV; for example, the major peak and satellite for the Eu L 3 edge are observed at 6972 and 6981 eV, respectively, as indicated by the vertical dashed lines. According to our previous Eu L 3 edge XAS study, 16 the major peak and satellite are attributable to the contributions from Eu 2+ and Eu 3+ ions, respectively. To estimate the relative contributions of Eu 2+ and Eu 3+ , the XAS for Eu L 3 edge was deconvoluted by the superposition of two Lorentzians and two arctangent functions, according to the procedure used by Godart et al 43 for the analysis of mixed valence in rare-earth intermediate compounds.…”
Section: Experimental Details and Sample Characteristicsmentioning
confidence: 65%
“…This idea is in agreement with the fact that the amorphization of EuTiO 3 crystal results in a decrease in the coordination number of Eu 2+ (12 in perovskite EuTiO 3 vs about 6 in a-ETO) as demonstrated by our previous analysis of x-ray absorption fine structure. 16 Namely, the reduction of coordination number of Eu 2+ upon amorphization makes the crystal field acting on Eu 2+ stronger in the amorphous phase than in the crystalline counterpart, resulting in the smaller 4f -5d energy separation for the former.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sol–gel,16–19 hydrothermal,20,21 and solvothermal22 synthesis, etc.). These nanopowders can be used for the preparation of the thin films by different deposition techniques such as dipping,17,18 low‐pressure hot target magnetron sputtering,23 or pulsed laser deposition 24. Previous works25 dealing with the preparation of glass‐like coatings on metallic substrates have unequivocally demonstrated that the use of EPD enabled the preparation of coatings with a greater thickness and increased density and uniformity than those obtained by simply dipping.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the procedure of measurement and analysis of EXAFS were described elsewhere. 30 Variation of magnetization with temperature and magnetic field was measured by using a superconducting quantum interference device (SQUID).…”
mentioning
confidence: 99%